2014
DOI: 10.1080/02673037.2013.873117
|View full text |Cite
|
Sign up to set email alerts
|

The Social Value of Housing in Straitened Times: The View from England

Abstract: This paper provides a commentary on the contemporary housing crisis in England and links it to broader questions of role of housing in capitalist economies and societies. It starts with the assumptions that housing and community development issues are linked to the wider housing market and that the housing crisis is not new but has long-run antecedents. The paper begins by reviewing the contemporary terrain of housing markets and policies in the UK. It then discusses several aspects of 'crisis': market volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…The research considers welfare reforms that have particular relevance for housing associations because they impact on Housing Benefit, which forms a majority component of rental income streams (Mullins & Jones, 2015). Table 1 summarizes these changes, whichalongside other measureswere presented by government as a response to perceptions of growing dependency and the increasing cost of welfare provision (Ferrari, 2015). Welfare reforms sought to, variously, reduce public spending on welfare, incentivize employment, and introduce 'fairness' between those in receipt of out-of-work benefits and those in employment (Mackley et al, 2018).…”
Section: The Housing Association Sector In Englandmentioning
confidence: 99%
“…The research considers welfare reforms that have particular relevance for housing associations because they impact on Housing Benefit, which forms a majority component of rental income streams (Mullins & Jones, 2015). Table 1 summarizes these changes, whichalongside other measureswere presented by government as a response to perceptions of growing dependency and the increasing cost of welfare provision (Ferrari, 2015). Welfare reforms sought to, variously, reduce public spending on welfare, incentivize employment, and introduce 'fairness' between those in receipt of out-of-work benefits and those in employment (Mackley et al, 2018).…”
Section: The Housing Association Sector In Englandmentioning
confidence: 99%
“…In July 2010, the newly elected Conservative-Liberal Democrat Coalition government in the UK published 21st Century Welfare (Department for Work and Pensions, 2010a), a consultation document on the reform of the benefits system. The analysis concluded that the existing system was too complex and presented disincentives to move into work which resulted in rising costs of welfare support and persistent welfare dependency (Ferrari, 2015). The principles and proposals set out in the consultation paper were detailed further in the White Paper, Universal Credit: Welfare that Works (Department for Work and Pensions, 2010b) and enshrined in law when the Welfare Reform Act 2012 (Department for Work and Pensions, 2012) received royal assent in March 2012.…”
Section: Universal Credit and The Direct Payment Of Housing Benefitmentioning
confidence: 99%
“…The existing system was perceived to be too complex and created disincentives for working-age claimants to move into paid work. The result, it was argued, had been rising costs of welfare support and persistent 'welfare dependency' (Ferrari, 2015). The principles and proposals set out in the consultation paper were detailed further in the White Paper, Universal Credit: Welfare that Works (Department for Work and Pensions, 2010b), and enshrined in law when the Welfare Reform Act 2012 (Department for Work and Pensions, 2012) received royal assent in March 2012.…”
Section: Welfare Reformmentioning
confidence: 99%